2018
DOI: 10.1371/journal.pone.0205854
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics in a cavity-nesting bee-wasp community: Shifts in composition, functional diversity and host-parasitoid network structure

Abstract: Ecological communities are composed of species that interact with each other forming complex interaction networks. Although interaction networks have been usually treated as static entities, interactions show high levels of temporal variation, mainly due to temporal species turnover. Changes in taxonomic composition are likely to bring about changes in functional trait composition. Because functional traits influence the likelihood that two species interact, temporal changes in functional composition and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 68 publications
1
16
1
1
Order By: Relevance
“…In line with hypothesis 3, the magnitude of seasonality in nest-building activity differed between functional groups, but in contrast to our assumption, it was synchronised in the colline zone with a strong peak at the end of the short rainy season for bees, caterpillar-and spiderhunting wasps. Seasonal patterns are believed to differ between species, families or other taxonomic groups (Wolda and Roubik 1986, Sirohi et al 2015, Osorio-Canadas et al 2018, but except for small differences, we rather found differences in magnitude than in seasonal timing of activity. A similar tendency was found in a leaf-roller community and herbivores seemed to fluctuate higher with seasonality than the predators (Vieira and Romero 2013).…”
Section: Synchronised Nesting-activity Between Bees and Wasps In The contrasting
confidence: 64%
See 1 more Smart Citation
“…In line with hypothesis 3, the magnitude of seasonality in nest-building activity differed between functional groups, but in contrast to our assumption, it was synchronised in the colline zone with a strong peak at the end of the short rainy season for bees, caterpillar-and spiderhunting wasps. Seasonal patterns are believed to differ between species, families or other taxonomic groups (Wolda and Roubik 1986, Sirohi et al 2015, Osorio-Canadas et al 2018, but except for small differences, we rather found differences in magnitude than in seasonal timing of activity. A similar tendency was found in a leaf-roller community and herbivores seemed to fluctuate higher with seasonality than the predators (Vieira and Romero 2013).…”
Section: Synchronised Nesting-activity Between Bees and Wasps In The contrasting
confidence: 64%
“…Seasonal changes in population size and species composition are presumably also reflected in the life-history traits of insect communities (Samnegård et al 2015, Osorio-Canadas et al 2018. For example, there are seasonal changes in the body size of bee communities (Osorio-Canadas et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Stress values below 0.2 indicated that the ordination adequately represented the data [32]. A measure of goodness of fit based on the Bray-Curtis dissimilarity index and distance in graphical representation was selected to evaluate the NMDS results, where the smaller the circle, the better goodness of fit [33].…”
Section: Methodsmentioning
confidence: 99%
“…Son bastantes y variadas las aportaciones que las redes han hecho a la ecología de estos grupos. Por ejemplo, Osorio-Canadas et al (2018), estudiaron las dinámicas estacionales en la composición y las redes antagonistas huéspedes-parasitoides en nidales artificiales y descubrieron que el servicio de polinización se veía maximizado en primavera mientras que el de depredación lo hacía en verano. En otro interesante artículo, Morris et al (2015) demostraron que las redes huésped-parasitoides pueden variar a lo largo del gradiente altitudinal en sistemas naturales.…”
Section: Redes Huésped -Enemigo Naturalunclassified